International trade law - Carr, Indira; Stone, Peter, 1947- (Oxon, Abingdon : Routledge, 2014)
"International Trade Law offers comprehensive analysis of international sale transactions through case law, policy documents, legislation, international conventions and rules adopted by international organisations such as the ICC. "--
Includes bibliographical references and index.
Keywords: Foreign trade regulation -- Great Britain